Life Cycle Assessment Research Trends and Implications: A Bibliometric Analysis - Moutik, Badr; Summerscales, John; Graham-Jones, Jasper; Pemberton, Richard (Sustainability, 2023)
Acknowledging the importance of sustainability and implementing measures to achieve the UN’s 17 Sustainable Development Goals (SDGs) by 2030 represent a holistic approach to promoting peace and prosperity for the planet and its inhabitants. LCA is a valuable tool for organisations to enhance sustainability and reduce environmental impact. There has been a notable increase in LCA research subjects, indicating a recognition of its significance in promoting sustainability. The field has experienced a significant expansion in the past decade, with a 30% annual percent growth rate in LCA publications since 2010. In the most recent 4 years alone, 47% of all LCA publications since 1991 were produced. This paper presents a comprehensive review of LCA research from 1991 to 2022, with a specific focus on the period from 2019 to 2022. The study identifies research avenues and trends in LCA research using diverse bibliometric analysis techniques alongside content examination and the SciVal topic clusters prominence indicator. This comprehensive approach reveals evolving trends, such as an increased emphasis on practical applications for global sustainability goals, LCA’s expansion into bio-based materials due to plastic pollution concerns, and quantification of circular economy benefits in solid waste management. Moreover, deeper exploration of energy-related sustainability aspects and the integration of LCA into early product development for eco-conscious design are observed. These trends signify widespread LCA adoption across industries to address energy and design-related sustainability challenges. The study acknowledges interdisciplinary collaboration among researchers, industry, and governments, shaping a robust LCA research landscape. China’s heightened contributions as a leading contributor to the field have reshaped the global LCA landscape mirrored in the evolving prominence of journals, institutes, and funding organisations.